ETIKA BISNIS ISLAM TERHADAP PENINGKATAN PENDAPATAN PEDAGANG ASONGAN DALAM ACARA SHOLAWATAN DI KABUPATEN MAGELANG: ETIKA BISNIS ISLAM TERHADAP PENINGKATAN PENDAPATAN PEDAGANG ASONGAN DALAM ACARA SHOLAWATAN DI KABUPATEN MAGELANG - Aisiyah, Nurul Aisiyah; M. Pudail; Qurotul Aini (An Nuqud Journal of Islamic Economics, 2025)
This study analyzes the application of Islamic business ethics by street vendors and consumer perceptions at sholawatan events in Magelang Regency, and its relation to income improvement. Employing a mixed-methods approach with questionnaires given to 50 vendors and 50 consumers, complemented by in-depth interviews, the research measures adherence to four Naqvi's ethical principles: Unity, Equilibrium, Free Will, and Responsibility. Results indicate that street vendors predominantly apply Islamic business ethics (100% on Unity and Responsibility, 92% Equilibrium, 85% Free Will), which is also perceived positively by most consumers. This ethical application is proven to contribute to vendors' income improvement through building trust and a positive reputation. This study not only provides a comprehensive understanding of business ethics practices in the religious-based informal sector but also fills a literature gap regarding microeconomic case studies in the context of local religious culture, offering a practical reference for vendors to achieve blessings and business sustainability.